PENGEMBANGAN GAME MOTI BERBASIS ANDROID PADA MATERI TRIGONOMETRI UNTUK SISWA SMA KELAS X - Lina Setiawati; Abd Qohar (JURNAL MATHEMATIC PAEDAGOGIC, 2020)
The research was aimed are to develop and to know the feasibility of Android-based MOTI game on trigonometry for tenth grade high school students. This development research uses the Plomp development model (2007) which includes three glass: preliminary research, prototyping phase, and assessment phase. The results showed that the media was declared valid with a validity score of 3.59, the validity score for student response questionnaire was 3.8, and the media practicality score was 3.5. Thus, the media in the form of Android-based games developed are feasible because meets valid and practical criteria.